Fatty acid profile of chaya (Cnidoscolus aconitifolius) leaves and fodder - Kumar, Anil; Or-rashid, Mamun M; Alzahal, Ousama; Mcbride, Brian W (The Indian Journal of Animal Sciences, 2011)
Chaya (Cnidoscolus aconitifolius) is a perennial shrub that is used as vegetable in Central America by the Maya people. The traditional knowledge also points to several medicinal properties of chaya. Being perennial in nature, yielding copious amount of foliage it can also be used as forage for livestock. The present study was carried out to determine the fatty acid profile of chaya leaves and fodder. Ether extract in chaya leaves and fodder were 9.27% and 3.61% of total dry matter, respectively. Chaya leaves had 58.9 g/ 100 g of total fatty acid,Â  polyunsaturated fatty acids (PUFA). The omega-3 (n-3) FA in chaya leaves was 50.0%. Chaya fodder had 42.6%Â  n-3 FA content. The n-3/ n-6 ratio in chaya leaves (5.6). A rare omega-3 PUFA in higher plants, eicosaterienoic acid (20:3n-3) was detected in chaya leaves (0.26% of total FA) and fodder (0.38% of total FA). One hundred g of fresh chaya leaves can provide about 50% of the Acceptable Intake of omega-3 fatty acids in human beings. Chaya fodder can provide an n-3 rich ration for cows and provide precursors for eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) rich milk. The medicinal properties attributed to chaya may be due to its fatty acid content. It was concluded that chaya has an optimal fatty acid profile for human consumption as well for healthy livestock production.